Primary productivity Based on Oxygen Method in the Betung Lake Betung Village Pangkalan Kuras Sub-District Pelalawan District Riau Province - Septriza Radella; Asmika Harnalin Simarmata; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPrimary productivity is the conversion of solar energy and nutrients to living biomass through photosynthesis. A research aimed to understand the primary productivity based on oxygen method was conducted in July-August 2019. There were three sampling stations namely Station 1 (inlet area), Station 2 (in the middle of the lake) and Station 3 (in the end of the lake). In each stations, there were 2 sampling point, in the surface (15 cm) and 2 Secchi (160 cm) depth. Sampling was done three times, once/week. Water quality parameters measured were temperature, pH, transparency, depth, dissolved oxygen, CO2, nitrate and phosphate concentration. Results shown that the temperature was 28.7-29 ºC, transparency was 81.3-84 cm, pH was 5, depth was 195-210 cm, DO was 3.87-6.12 mg/L, CO2 was 6.27-15.42 mg/L, nitrate was 0.0229-0.0405 mg/L, and phosphate was 0.0226-0.0406 mg/L. Primary productivity based on oxygen method in the Betung Lake was 158-349 gC/m3/Day and it can be categorized mesotrophic.  Keywords : Oxbow Lake, Photosynthesis, Water Quality, Nilo River,Transparency